2018
DOI: 10.1021/acs.est.8b00033
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Trends of Elemental Carbon and Char/Soot Ratios in Five Sediment Cores from Eastern China Marginal Seas: Indicators of Anthropogenic Activities and Transport Patterns

Abstract: Elemental carbon (EC), the highly recalcitrant carbonaceous material released exclusively from fossil fuel combustion and biomass burning, is a preferred geochemical agent for evaluating anthropogenic activities. We investigated the spatiotemporal trends of EC and char/soot ratios (char and soot, the two subtypes of EC, differ in formation mechanisms and physicochemical characteristics) in five sediment cores from eastern China marginal seas, spatially spanning from inshore coastal mud areas to offshore remote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 59 publications
(157 reference statements)
5
39
0
Order By: Relevance
“…To date, there have been plenty of investigations concerning PBC on the regional atmosphere, soils, sediments, and coastal wetlands in Bohai Rim (Li and Bai, 2009;Liu et al, 2011;Chen et al, 2013;Huang et al, 2014;Andersson et al, 2015;Fang et al, 2015;Zhang et al, 2015;Fang et al, 2016;Liu et al, 2016;Xu et al, 2017;Fang et al, 2018b;Shao et al, 2018). In comparison, however, the available studies draw relatively less attention on PBC in the aquatic environments (such as the riverine water and coastal seawater), let alone the analytically highly complicated and challengeable DBC (Wang et al, 2016;Xu et al, 2016;Fang et al, 2018a;Qi et al, 2020;Fang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…To date, there have been plenty of investigations concerning PBC on the regional atmosphere, soils, sediments, and coastal wetlands in Bohai Rim (Li and Bai, 2009;Liu et al, 2011;Chen et al, 2013;Huang et al, 2014;Andersson et al, 2015;Fang et al, 2015;Zhang et al, 2015;Fang et al, 2016;Liu et al, 2016;Xu et al, 2017;Fang et al, 2018b;Shao et al, 2018). In comparison, however, the available studies draw relatively less attention on PBC in the aquatic environments (such as the riverine water and coastal seawater), let alone the analytically highly complicated and challengeable DBC (Wang et al, 2016;Xu et al, 2016;Fang et al, 2018a;Qi et al, 2020;Fang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Black carbon (BC) is a highly aromatic, recalcitrant carbon species released both from the wildfire and anthropogenic fire for the main energy utilization in ancient human civilization. It has two subtypes, char and soot (8,9), which can be distinguished by thermal optical reflectance due to their different burning temperatures (10,11). BC is widely distributed in lake and ocean sediments via transportation by atmospheric circulation and surface runoff (12).…”
Section: Introductionmentioning
confidence: 99%
“…Char particles (1~100 µm) are residues of combustion at temperatures of 300~600℃ that retain some of the morphological and structural features of their precursors, and are a function of biomass burning. Soot particles (< 1 µm) are produced during high-temperature combustion (> 600℃), which is strongly related to anthropogenic fuels (e.g., petroleum, coal, and charcoal) or highintensity biomass burning (8,9,10,13,14,15). The sedimentary records of char and soot can provide information for tracking past changes in fire activity forced by climate change or human activities on multi-decadal to millennial scales (16).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A coating of brown carbon (BrC) can further amplify the light absorption compared to a transparent coatings (Lack and Cappa, 2010). Recent studies suggested that BC mixing state diversity also affects the bulk E abs (Fierce et al, 2016;Matsui et al, 2018;Cappa et al, 2019).…”
Section: Introductionmentioning
confidence: 99%